2023
DOI: 10.1002/advs.202301914
|View full text |Cite
|
Sign up to set email alerts
|

Enantiopure Dinaphtho[2,3‐b:2,3‐f]thieno[3,2‐b]thiophenes: Reaching High Magnetoresistance Effect in OFETs

Abstract: Chiral molecules are known to behave as spin filters due to the chiral induced spin selectivity (CISS) effect. Chirality can be implemented in molecular semiconductors in order to study the role of the CISS effect in charge transport and to find new materials for spintronic applications. In this study, the design and synthesis of a new class of enantiopure chiral organic semiconductors based on the well‐known dinaphtho[2,3‐b:2,3‐f]thieno[3,2‐b]thiophene (DNTT) core functionalized with chiral alkyl side chains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Therefore, as an explanation for the apparent violation of Onsager nonreciprocity by CISS-MR close to thermal equilibrium, one must conclude that the Onsager relation does not apply to the electrical transport in CISS-MR devices with thin chiral layers, implying that this transport is not diffusive. Such an explanation would be consistent with recent observations of CISS-MR in macroscopic chiral field-effect devices, which are clearly in the diffusive transport regime, and where “eMChA-like” asymmetry in the I – V curves is reported …”
supporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, as an explanation for the apparent violation of Onsager nonreciprocity by CISS-MR close to thermal equilibrium, one must conclude that the Onsager relation does not apply to the electrical transport in CISS-MR devices with thin chiral layers, implying that this transport is not diffusive. Such an explanation would be consistent with recent observations of CISS-MR in macroscopic chiral field-effect devices, which are clearly in the diffusive transport regime, and where “eMChA-like” asymmetry in the I – V curves is reported …”
supporting
confidence: 91%
“…In particular, two-terminal devices consisting of chiral molecular layers between ferromagnetic contacts have shown quite strong effects. Some discussion as to the possible role of CISS in such observations has arisen, , but most experimental reports agree on the phenomenology of antisymmetric I – V curves, where the current is an odd function of the voltage (i.e., I ( V ) = − I (− V )), that are different for the two directions of longitudinal magnetization of the ferromagnetic contacts and that are different for the two handednesses of the chiral layer. It should be noted that a few diverging reports exist, both in junction devices and in field effect transistors . Some theoretical microscopic models also predict I – V curves that are strictly odd in V , but other models predict “eMChA-like” I – V curves that contain V -even terms or both .…”
mentioning
confidence: 99%
“…A chirality-dependent asymmetry in the MR of the ferromagnet is found that is independent of the applied current, showing that coupling between (molecular) chirality and ferromagnetism can induce an effect on the measured MR that is not current-dependent. This could also be relevant for measurements of adhesion forces between chiral systems and ferromagnets , (with different magnetization directions) as well as in field-effect transistor devices with a chiral channel or other experiments involving electrostatic gating of a chiral system. This shows that the electrostatic interactions between chiral systems and ferromagnets can be a widely applicable phenomena with important fundamental physics to be explored as well as possible application in nanotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…60 However, it has been clearly observed in a number of experiments. 19−21 Another recent experiment by Volpi et al 61 has investigated field effect transistors with a chiral semiconductor channel and ferromagnetic source and drain electrodes. It was found that the threshold gate voltage is strongly modified by the magnetization direction, highlighting the significance of electrostatic effects for chiral systems coupled to a ferromagnet.…”
Section: Magnetochiral Contact Potential Modificationmentioning
confidence: 99%
“…Thiophene, a five-membered aromatic ring similar to benzene, possesses a distinctive cyclic structure that imparts it with high electron density and strong conjugation effects. [44,45] Thiophene and its derivatives have found applications in pharmaceuticals, [46] materials science, [47] and organic optoelectronic devices. [48] By introducing thiophene units into cMOFs, exciting electrical performance can be achieved.…”
mentioning
confidence: 99%